MARAKNYA ANGKATAN KERJA KONTRAK MENGAKIBATKAN KURANG NYA KESEJAHTERAAN HIDUP PARA PEKERJA - Meiziya Asira Deliyanti; Mirna Nur Alia Abdullah (SABANA: Jurnal Sosiologi, Antropologi, dan Budaya Nusantara, 2024)
This research aims to determine the welfare of the contract workforce which is different from the welfare of the permanent workforce, which includes wages, severance pay and working time. The workforce has an important role for Indonesia's economic progress. The research method used is the literature review method, which was obtained from journals related to the topic and already published. The results of this research show that there are still many workers who do not receive their rights as workers in accordance with the Employment Law. The company also ignores the rights that contract workers should have. The workforce is obliged to think about their future, as a result of this contract workforce they can experience an uncertain future, sudden layoffs. So, the government is advised to review the Employment Law. The conclusion is that contract labor is not always associated with negative impacts, but if the company can work together with the workforce, it will achieve the welfare of life that the workforce wants to achieve.